1983
DOI: 10.1111/j.1365-2621.1983.tb05053.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Soda Leavening on Phytic Acid Content and Physical Characteristics of Middle Eastern Breads

Abstract: The effect of soda (sodium bicarbonate) as a leavening agent on pH, phytic acid hydrolysis and physical quality of a fermentation model system and two popular Middle Eastern breads, Iranian taftoon and Pakistani naan (Arabic) were studied. Supplementing 0.2 and 0.4% soda invariably decreased phytic acid hydrolysis. In sour starter supplemented dough, phytic acid was reduced by 82% after 3 hr. However, when 0.4% soda and sour starter were added loss of phytic acid did not exceed 29%. Supplementing soda in tafto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1987
1987
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…The results presented in Table 2 show that 32.4% of the original phytic acid was lost during the preparation of Arabic bread when regular fine bran was used. This decrease in phytic acid is comparable to that reported by Faridi et al (1983) who showed that 22% of the original phytic acid was lost during the preparation of yeastleavened Naan (Arabic) bread made from 100% extraction flour. Preincubation of the bran in a limited volume of water before incorporating it in the bread preparation formula did not cause any noticeable change in the phytic acid levels.…”
Section: High Bran Breadsupporting
confidence: 91%
“…The results presented in Table 2 show that 32.4% of the original phytic acid was lost during the preparation of Arabic bread when regular fine bran was used. This decrease in phytic acid is comparable to that reported by Faridi et al (1983) who showed that 22% of the original phytic acid was lost during the preparation of yeastleavened Naan (Arabic) bread made from 100% extraction flour. Preincubation of the bran in a limited volume of water before incorporating it in the bread preparation formula did not cause any noticeable change in the phytic acid levels.…”
Section: High Bran Breadsupporting
confidence: 91%
“…Other effects on dough properties. Compared to yeasted bread, supplementing dough with sodium bicarbonate would increase its water absorption and reduce phytic acid hydrolysis (Faridi et al ., 1983). In acid‐free dough, gas production rate by sodium bicarbonate decreases because pH progressively becomes more alkaline (Matz, 1987a).…”
Section: Gas‐releasing Agentsmentioning
confidence: 99%